Complex symmetry of weighted composition operators on the Fock space - Hai, Pham Viet (2015)
With the techniques of weighted composition operators, we introduce a new concept of general weighted composition conjugations on the Fock space F2(C) and completely solve the following problems: the description of weighted composition operators which are conjugations; the criteria for weighted composition operators to be complex symmetric; the spectrum and the point spectrum of complex symmetric operators; and the criteria for Schatten class membership as well as for normality of such operators.